Extraction Of Phytochemicals In Morinda citrifolia L. Leaves By Using Different Polarity Solvents - Asman, Saliza; Mohd Zin, Siti Rabaah (Enhanced Knowledge in Sciences and Technology, 2023)
Morinda citrifolia L. is known to have anti-inflammatory, antibacterial, antifungal, and antioxidant benefits due to its many phytochemical compounds present. Therefore, this research was conducted to determine the best solvent for the extraction of phytochemicals in M. citrifolia leaves by comparing three different solvents. The leaves powder was macerated respectively in three different polarity solvents which was dichloromethane, ethyl acetate, and n-hexane for 3 days. Dichloromethane had the highest percentage yield of extraction (75.00%), followed by ethyl acetate (18.89%) and n-hexane with the lowest percentage yield (5.06%). This research found ethyl acetate as the best solvent for the extraction of phytochemicals in M. citrifolia leaves due to its ability to dissolve a wide range of compounds, both polar and nonpolar compounds present in the plant material.